Are blockchains immune to all malicious attacks? - Jennifer J. Xu (Financial Innovation, 2016)
Background: In recent years, blockchain technology has attracted considerable attention. It records cryptographic transactions in a public ledger that is difficult to alter and compromise because of the distributed consensus. As a result, blockchain is believed to resist fraud and hacking. Results: This work explores the types of fraud and malicious activities that can be prevented by blockchain technology and identifies attacks to which blockchain remains vulnerable. Conclusions: This study recommends appropriate defensive measures and calls for further research into the techniques for fighting malicious activities related to blockchains.
Keywords: 650; Blockchain; Online malicious attacks; Fraud detection; Hacking prevention